2012
DOI: 10.3109/00207454.2012.672501
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood Flow Patterns in Patients With Freezing of Gait Due to Lacunar Infarction: SPECT Study Using Three-Dimensional Stereotactic Surface Projections

Abstract: These results suggest that anterior cingulate cortex dysfunction may be involved in the pathology of FOG in patients with chronic lacunar infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Interestingly, a SPECT study on patients with FOG due to vascular parkinsonism (VP) found significant reduction in the perfusion of the right parietal cortex and bilateral ACC [ 12 ].…”
Section: Pet and Spectmentioning
confidence: 99%
“…Interestingly, a SPECT study on patients with FOG due to vascular parkinsonism (VP) found significant reduction in the perfusion of the right parietal cortex and bilateral ACC [ 12 ].…”
Section: Pet and Spectmentioning
confidence: 99%